0023 Using the new title v MCH national performance measure 7 to reduce injury-related hospitalizations among children and adolescents ages 0–19. (26th April 2015) - Reiney, Erin; Allison, Jennifer; Hunt, Rebekah
Abstract : Statement of purpose: Every year, one in nine young people is injured seriously enough to require medical attention, and nearly 320, 000 injury-related hospitalizations occur. Injuries are a leading cause of medical spending for children and adolescents, a burden estimated at $4 billion in annual healthcare costs for hospitalizations alone. By focusing on the reduction of injury-related hospitalizations, public health professionals can significantly reduce the toll of injuries in the U.S. Methods/Approach: The Health Resources and Services Administration's Maternal and Child Health Bureau has proposed the reduction of injury-related hospitalizations among infants, children, and adolescents ages 0 through 19 as one of 15 possible National Performance Measures (NPMs) for inclusion in the Title V Maternal and Child Health Services Block Grant Program. This presentation will describe this new NPM and explain the opportunity that it provides for improving the health and safety of infants, children, and adolescents. Results: Presenters will explain the burden of injury-related hospitalizations in the U.S.; describe the new Title V Maternal and Child Health (MCH) Performance Measure framework and how it is related to the 5-year Needs Assessments that state MCH programs are currently conducting; provide an overview of ways to get involved in the Needs Assessment process and the selection of injury-related NPMs; and share Children's Safety Network (CSN) resources on effective strategies for reducing injury-related hospitalizations. Conclusions: Participants will be equipped to use the new injury hospitalisation NPM to address a range of important injury issues, including falls, motor vehicle crashes, prescription drug overdoses, suicide, homicide, drowning, and sudden and unexpected infant death. They will also have an opportunity for interactive discussion about ways for state injury prevention programs to collaborate with state MCH programs on the selection of evidence-based strategies to address the injury hospitalisation NPM. Significance and contribution to the field: The new Title V MCH Performance Measure framework provides injury prevention professionals with new opportunities to leverage existing partnerships and build new alliances to advance effective policies and practices for reducing injury-related hospitalizations. This presentation will enable participants to capitalise on those opportunities and make injury prevention a state and national priority.